The Landscape Research Centre - Landscape Research Centre (2011)
[Dt.:] Das Ziel des "Centre" ist es, die Forschung der Landschaftsevolution von dem Paleolithikum bis zur Gegenwart zu fördern. Die Webseite enthält auch ein Blog zu aktuellen Projekten der Luftbildarchäologie und der Geoarchäologie in Großbritannien und bietet Kartenmaterial und 3D-Modelle, unter [https://thelrc.wordpress.com/]. - [Engl.:] The aims of the Landscape Research Centre is to promote research into the evolution of the landscape from the Palaeolithic to the present, and to publish the results. The Centre's weblog informs about recent aerial archaeology and geoarchaeological projects in Great Britain including maps and 3d models [https://thelrc.wordpress.com/].